2018
DOI: 10.1186/s12917-018-1580-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for recurrence of FMD outbreaks in Iran: a case-control study in a highly endemic area

Abstract: BackgroundFoot-and-mouth disease (FMD) is an acute viral disease of cloven-hoofed animals with high economic impact. FMD remains endemic in Iran particularly in the livestock-dense province of Khorasan Razavi in northeastern Iran where FMD outbreaks continuously occur. In this study, we aimed to quantify risk factors for the recurrence of FMD outbreaks in Iran by analyzing a time-series of FMD outbreak data from the province of Khorasan Razavi.ResultsThis study used FMD outbreak data collected from 2012 to 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 27 publications
1
11
0
Order By: Relevance
“…[11] on the knowledge, attitude and practice of this population of farmers in regard to infectious diseases, it can be concluded that the poor practice and lack of knowledge of biosecurity and infectious diseases among pastoralists are potential contributors to the high prevalence of infectious diseases in sheep and goats in Iran. This conclusion is consistent with the findings of a recent study on Iranian dairy cattle farms that identified inappropriate biosecurity practices as a major cause of mortality and morbidity [17] and those of Hosein Abadi et al [18], who concluded that high abortion rates on sheep farms in south-east Iran were related to poor biosecurity measures. It should be mentioned that a probable source of bias in this study was the sampling method (snowball sampling) and the limited number of geographical regions studied.…”
Section: Practicing Preventive Measures By Farmers Comes At a Costsupporting
confidence: 92%
“…[11] on the knowledge, attitude and practice of this population of farmers in regard to infectious diseases, it can be concluded that the poor practice and lack of knowledge of biosecurity and infectious diseases among pastoralists are potential contributors to the high prevalence of infectious diseases in sheep and goats in Iran. This conclusion is consistent with the findings of a recent study on Iranian dairy cattle farms that identified inappropriate biosecurity practices as a major cause of mortality and morbidity [17] and those of Hosein Abadi et al [18], who concluded that high abortion rates on sheep farms in south-east Iran were related to poor biosecurity measures. It should be mentioned that a probable source of bias in this study was the sampling method (snowball sampling) and the limited number of geographical regions studied.…”
Section: Practicing Preventive Measures By Farmers Comes At a Costsupporting
confidence: 92%
“…This study (Table 5) highlighted the increased risk through direct and indirect contacts of livestock (movement of cattle to and from animal markets and farmers’ attendance at the animal and animal product market) for infection of herds. Unrestricted animal movements are considered the major contributor to the endemic status of FMD in the Asian region, especially in Pakistan and Iran, which border Afghanistan (Emami et al., 2015; Ilbeigi et al., 2018; Jamal et al., 2010), along with other Asian countries that Afghanistan has trade agreements with, such as India (Pattnaik et al., 2012; Subramaniam et al., 2013). It is widely accepted that the greatest risk for the spread of FMD arises from the movement of infected animals (Alexandersen et al., 2003), and this was highlighted in the current study with farmers who introduced cattle into their herd in the 12‐month period preceding the study being 2.6 times more likely to have an infected herd.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports indicated that limited vaccination coverage [29] or inconsistent FMD vaccination programs [35] were risk factors for FMD outbreaks. In this study, we examined the effects of vaccine Animals 2020, 10, 512 9 of 12 administration because vaccination programs were applied three times a year to all dairy farms as recommended by the DLD [36].…”
Section: Discussionmentioning
confidence: 99%